2015
DOI: 10.1051/0004-6361/201424548
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of gyrosynchrotron emission polarization from solar flares by sausage modes: forward modeling

Abstract: We examined the polarization of the microwave flaring emission and its modulation by the fast sausage standing wave using a linear 3D magnetohydrodynamic model of a plasma cylinder. We analyzed the effects of the line-of-sight angle on the perturbations of the gyrosynchrotron intensity for two models: a base model with strong Razin suppression and a low-density model in which the Razin effect was negligible. The circular polarization (Stokes V) oscillation is in phase with the intensity oscillation, and the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The sausage oscillations within short periods (<60 s) are often decayless or weakly damping when the cutoff condition and those within long periods (>60 s) are substantially compressible and transverse (Gruszecki et al 2012;Vasheghani Farahani et al 2014;Tian et al 2016). Moreover, they could produce density variation, which can easily modulate the periodic oscillations in microwave emission (Rosenberg 1970;Aschwanden 2005;Antolin & Van Doorsselaere 2013;Reznikova et al 2015). The loop oscillations here are incompressible, damping, and no corresponding intensity fluctuations are detected in EUV and microwave emissions.…”
Section: Mhd Wavesmentioning
confidence: 98%
“…The sausage oscillations within short periods (<60 s) are often decayless or weakly damping when the cutoff condition and those within long periods (>60 s) are substantially compressible and transverse (Gruszecki et al 2012;Vasheghani Farahani et al 2014;Tian et al 2016). Moreover, they could produce density variation, which can easily modulate the periodic oscillations in microwave emission (Rosenberg 1970;Aschwanden 2005;Antolin & Van Doorsselaere 2013;Reznikova et al 2015). The loop oscillations here are incompressible, damping, and no corresponding intensity fluctuations are detected in EUV and microwave emissions.…”
Section: Mhd Wavesmentioning
confidence: 98%
“…The codes calculate the emission characteristics by numerical integration of the radiative transfer equations for the ordinary and extraordinary electromagnetic modes while taking into account the possible mode-coupling effects, i.e., interaction between the modes in the regions of transverse magnetic field (Cohen, 1960;Zheleznyakov and Zlotnik, 1964). This approach is sufficient to reproduce accurately the emission intensity in both the quasi-longitudinal and quasi-transverse (with respect to the magnetic field) propagation regimes as well as the circular polarization in the quasi-longitudinal regime (Nita et al, 2015), although simulating the polarization in the regions with θ ≃ 90 • may require considering the full set of Stokes parameters (see the upcoming paper of Reznikova, Van Doorsselaere, and Kuznetsov (2015)). Only the emission and absorption processes inside the curved magnetic loop are considered, i.e., the emission outside the loop is assumed to propagate like in vacuum.…”
Section: Electron Parametersmentioning
confidence: 99%
“…They found that the LOS effect and spatial resolution could significantly affect the intensity modulation and spectral characteristics of the fast sausage mode. Reznikova et al (2014Reznikova et al ( , 2015 used the same model and further investigated the gyrosynchrotron emission intensity variation using the fast gyrosynchrotron codes (Fleishman & Kuznetsov 2010). The radio emission intensity of the fast sausage mode oscillates in phase for all frequencies, while for certain LOS angles, the optically thick and thin radio emissions are antiphase.…”
Section: Introductionmentioning
confidence: 99%